A walk through a lost treasure: The house of Shaykh al-Sadat al-Wafaâ'iyya - Ahmed, Norhan (AUC Knowledge Fountain, 2020)
Cairo “having turned into a provincial town under the Ottoman rule - lost the glorious status it had enjoyed during the Mamluk period. That affected the functions of the city resulting in changes of its architecture. In particular, stripped of its role of the capital and military center, Cairo metamorphosed into a hub of commercial activities attracting mainly merchants and travelers. Such a transformation affected the domestic architecture of the Ottoman period. According to Andre Raymond, the wealthier Ottoman houses were arranged near the center, and the poor were located further away. The socio-economic levels of inhabitants of Cairo under Ottoman rule were disparate, which predetermined a type of housing depending on dwellers' needs. Some of the Cairene houses at that period were so small that they were barely large enough for a family to spend a night in. A house for such a family was not much more than a shelter; for others, the house represented the prestige and the social state of the family. Based on the social and economic stratum, Nelly Hanna classified Ottoman domestic architecture in Cairo into three types: houses (upper class), rental housing units (middle-class), and shared dwellings (lower class). This research focuses on the upper-class houses, also known as private dwellings. The primary interest of the study is in the Birkat al-Fil area, as well as Birkat al-Azbakiyya. Historians were more concerned with categorizing the domestic architecture of Cairo into strata; however, there is a category that has not received proper attention. This category encompasses the waterfront houses. Birkat al-Azbakiyya and Birkat al-Fil were the largest birkas in Cairo that used to display unique architectural treatment for the buildings surrounding them. Moreover, they were occupied by distinguished occupants. According to Hanna, birkas usually had qusur surrounding them. However, some of those birkas were surrounded by luxurious houses that were not at the same level as qusur. Birkat al-Fil was considered one of the prime locations of those elite houses. Being the residential area of highly ranked figures - such as amirs - and princely houses, it was one of the exceptions because it was not a densely settled area. Moreover, the architecture of those houses was distinguished since their main rooms overlooked the water. Unfortunately, almost nothing has remained of those palaces. Yet, the French architecturally documented one of these houses - that of Hasan al-Kashif - and sketched elements of other houses, for instance, that of Uthman Bay. Besides, one of such upper-class waterfront houses still exists in a fragmental state. This house used to be known as the house of Shaykh al-Sadat al-Wafa'iyya. This thesis aimed at identifying to what extent the architectural approach to waterfront houses was different from the approach to upper-class houses. It also intended to study the house of Shaykh al-Sadat in light of the social and economic strata of the Wafa'iyya family. With the availability of the waqfiyya of Shaykh Abu'l-Anwar al-Sadat and sketches by contemporary orientalists, it has been possible to document the key elements of this house. Furthermore, since this house used to be an upper-class residence, it is possible to compare it with still existing upper-class Ottoman houses in order to classify the unique features that were introduced in this house. This comparison will suggest that the house of Shaykh al-Sadat was unique and reflected the economic, political and social state of the Wafa'iyya family. Moreover, this research aims at reconstructing the house of Shaykh al-Sadat based on the availability of the waqfiyya, and the work of contemporary scholars and artists. By consulting more recent historians, sources that include the description of the current state of the house, and the primary sources, the research can suggest a complete layout of the original state of the house. The Ministry of Antiquities previously offered a reconstruction proposal based on the archeological traces, and investigations done by the Comit-©. This can now be corrected based on the data collected in this thesis.